2013
DOI: 10.1177/0269215513494229
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled pilot study of customized pamphlets to promote physical activity and symptom self-management in women with multiple sclerosis

Abstract: This pilot study indicates that a customized print-based intervention shows promise in improving physical activity levels and health and function in women with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 23 publications
0
70
0
Order By: Relevance
“…Finally, brochures have also helped individuals increase physical activity. 25,26 Several factors may have contributed to the equal success of all 3 programs. All interventions were theory based.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, brochures have also helped individuals increase physical activity. 25,26 Several factors may have contributed to the equal success of all 3 programs. All interventions were theory based.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators who used theory to drive the development of behavior change interventions also observed positive behavior changes. [17][18][19][23][24][25][26] Glanz et al referred to a number of systematic reviews of interventions and concluded that the use of health behavior theory is essential in producing effective interventions. 33 Message framing may have exerted an influence on increased calcium and vitamin D intakes in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, tailored unsupervised interventions can be a viable option for individuals with certain types of disabilities. Plow and colleagues, for example, demonstrated the preliminary efficacy of a tailored intervention to promote PA among women with multiple sclerosis (70). …”
Section: Pa Promotion Among Individuals With Physical Disabilitiesmentioning
confidence: 99%
“…Thirty (30) adult females with a physician confirmed diagnosis of relapsing-remitting multiple sclerosis volunteered to participate in this study (48 ± 9 years old; mean ± SD); all PwMS were recruited from a randomized controlled pilot trial [16]. The average duration from time of diagnosis was 9 ± 7 years and the average duration from onset of symptoms was 14 ± 8 years.…”
Section: Methodsmentioning
confidence: 99%